A ação vocal nos leitores text-to-speech - Camargo, Ana Paula Leite de (2012)
This paper aims to investigate the main characteristics of the vocal action (intonations of speech) and its possible application in a text-to-speech software (screen readers) according to the score of the voice in Gayotto (2002). Thus, we observed: orality in Classical Greece and the transformation that literacy gave the Western world supported by the speech of McLuhan; the evolution of storage of documents produced, highlighting the libraries through Darnton; the evolution of libraries by Marchiori from the traditional to the virtual and digital; access to digital information and the perception and cognition of congenital and acquired blind people examined in reports of Merleau-Ponty and Sacks, to understand how these subjects have access to information; the vocal action realization reading a text Gayotto and differences between intonational and monotonal reading; assistive technologies available in audio, such as the audiobook, the talking book and screen reader the former allows the realization of vocal action, in contrast to the screen readers which normally perform a dull and, in a sense, quite poor reading in their interpretation; technical specifications required to have an accessible online environment and accessibility standards of the W3C that categorizes the web with the intention of making it accessible to all without exception; validation of accessibility in virtual and digital libraries in Brazil and finally, noted the issue of non-neutrality of technology, through texts from Heidegger (2001) and Abranches (1996). In the end it is suggested that a reading with a vocal action contributes significantly to enrich the interpretation of the text and thus enables the listener an experience with richer semantics